2015
DOI: 10.1117/12.2076681
|View full text |Cite
|
Sign up to set email alerts
|

Photocathode electron beam sources using GaN and InGaN with NEA surface

Abstract: A photocathode electron source using p-type GaN and p-type InGaN semiconductors with a negative electron affinity (NEA) surface has been studied for its ability to maintain an extended NEA state. The key technology of NEA photocathodes is the formation of electric dipoles by atoms on the surface, which makes it possible for photo excited electrons in the conduction band minimum to escape into the vacuum. This means that in order to keep the electron energy spread as small as possible, the excitation photon ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…14) Damaging the surface increases the affinity of the surface to a positive value and the tunneling probability significantly decreases. Machuca and co-workers, 15,16) and our previous studies 17,18) have revealed that the NEA states of wide-gap semiconductors such as GaN and InGaN are more robust than those of GaAs.…”
Section: Introductionmentioning
confidence: 74%
“…14) Damaging the surface increases the affinity of the surface to a positive value and the tunneling probability significantly decreases. Machuca and co-workers, 15,16) and our previous studies 17,18) have revealed that the NEA states of wide-gap semiconductors such as GaN and InGaN are more robust than those of GaAs.…”
Section: Introductionmentioning
confidence: 74%
“…In some cases, QEs of well over 20% have been reported for NEA treated GaN-based photocathodes under UV illumination. Various reports suggest that certain properties of GaN-based semiconductors can be tailored to enhance photoemission including band gap engineering 122,123 , doping 124,125 , utilizing inherent polarization fields 124 , nanowire structures 126 , quantum well structures 122,123 , and heterojunction schemes 119,127 . Some of these reports show promising results for limited application areas, but systematic investigations are lacking and there is limited information regarding photocathode lifetimes and no information on emittance measurements.…”
Section: Advanced Thin Film Semiconductors and Band Gap Engineering Omentioning
confidence: 99%
“…11 However, because the NEA surface of a GaAs photocathode is sensitive to surface damage, the vacuum pressure must be lower than 10 −9 Pa, making such photocathode difficult to be used in industrial equipment operating at a vacuum pressure higher than 10 −9 Pa. On the other hand, wide-gap semiconductors, such as GaN and InGaN, are attractive candidates for industrial applications because of their high stability and more than 10 times longer QE lifetime than GaAs. 12,13 An InGaN is suitable for industrial use because of the availability of a visible laser as an excitation light source and transmission-type structure. 14 The following are the three goals of this study.…”
Section: Introductionmentioning
confidence: 99%